Photophysical and Antibacterial Properties of Porphyrins Encapsulated inside Acetylated Lignin Nanoparticles - Nidia Maldonado-Carmona; Tan-Sothea Ouk; Nicolas Villandier; Claude Alain Calliste; Mário J. F. Calvete; Mariette M. Pereira; Stéphanie Leroy-Lhez (MDPI AG, 2021)
Lignin has recently attracted the attention of the scientific community, as a suitable raw material for biomedical applications. In this work, acetylated lignin was used to encapsulate five different porphyrins, aiming to preserve their photophysical properties, and for further use as antibacterial treatment. The obtained nanoparticles were physically characterized, through dynamic light scattering size measurement, polydispersity index and zeta potential values. Additionally, the photophysical properties of the nanoparticles, namely UV-vis absorption, fluorescence emission, singlet oxygen production and photobleaching, were compared with those of the free porphyrins. It was found that all the porphyrins were susceptible to encapsulation, with an observed decrease in their fluorescence quantum yield and singlet oxygen production. These nanoparticles were able to exert an effective photodynamic bactericide effect (blue-LED light, 450-460 nm, 15 J/cm2) on Staphylococcus aureus and Escherichia coli. Furthermore, it was achieved a photodynamic bactericidal activity on an encapsulated lipophillic porphyrin, where the free porphyrin failed to diminish the bacterial survival. In this work it was demonstrated that acetylated lignin encapsulation works as a universal, cheap and green material for the delivery of porphyrins, while preserving their photophysical properties.